Blockade of cholinergic transmission elicits somatic signs in nicotine-naïve adolescent rats - Schmidt, Clare E.; Manbeck, Katherine E.; Shelley, David; Harris, Andrew C. (Frontiers in Pharmacology, 2015)
High doses of the nicotinic acetylcholine receptor (nAChR) antagonist mecamylamine can elicit somatic signs resembling those associated with nicotine withdrawal in nicotine-naïve adult rats. Understanding this phenomenon, and its possible modulation by acute nicotine and age, could inform the use of mecamylamine as both an experimental tool and potential pharmacotherapy for tobacco dependence and other disorders. This study evaluated the ability of high-dose mecamylamine to elicit somatic signs in adolescent rats, and the potential for acute nicotine pretreatment to potentiate this effect as previously reported in adults. Single or repeated injections of mecamylamine (1.5 or 3.0 mg/kg, s.c.) elicited somatic signs in nicotine-naive adolescents, but this effect was not influenced by two hour pretreatment with acute nicotine (0.5 mg/kg, s.c.). In an initial evaluation of the effects of age in this model, mecamylamine (2.25 mg/kg, s.c.) elicited somatic signs in nicotine-naive adolescents and adults. This effect was modestly enhanced following acute nicotine injections in adults but not in adolescents, even when a higher nicotine dose (1.0 rather than 0.5 mg/kg, s.c.) was used in adolescents to account for age differences in nicotine pharmacokinetics. These studies are the first to show that mecamylamine elicits somatic signs in nicotine-naïve adolescent rats, an effect that should be considered when designing and interpreting studies examining effects of high doses of mecamylamine in adolescents. Our findings also provide preliminary evidence that these signs may be differentially modulated by acute nicotine pretreatment in adolescents versus adults.